2012
DOI: 10.1007/s40291-012-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Therapeutic Response to BCL2 Antagonists in Cancer

Abstract: Cancer cells persist by resisting programmed cell death or apoptosis. In particular, an imbalance of proteins that regulate apoptosis leads to lack of response to apoptotic stimuli. Thus, restoring the ability of cancer cells to undergo apoptosis is highly desirable. One apoptosis pathway, the intrinsic pathway, involves perturbation of the mitochondria. The major players of this pathway are the members of the B cell CLL/lymphoma 2 (BCL2) family. Currently, three BCL2 antagonists are in clinical trials for can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Others have shown that SCLC cell lines are sensitive to treatment with navitoclax (ABT-263), a dual inhibitor of BCL2 and BCLxl (22). In contrast, other solid tumors were shown to depend mainly on BCLxl and MCL1 but not BCL2 for survival (34). The role of MCL1 in BET inhibitor sensitivity in SCLC cells is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that SCLC cell lines are sensitive to treatment with navitoclax (ABT-263), a dual inhibitor of BCL2 and BCLxl (22). In contrast, other solid tumors were shown to depend mainly on BCLxl and MCL1 but not BCL2 for survival (34). The role of MCL1 in BET inhibitor sensitivity in SCLC cells is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The link between overexpressed anti-apoptotic BCL-2 family proteins and cancer is now well established [4]. Enhanced expression of these proteins has been reported in numerous cancers, which permits cell growth and survival in the presence of apoptotic signals associated with the transformed phenotype, and can also lead to the failure of chemotherapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The role of anti-apoptotic BCL-2 family proteins in various cancers has been well studied [ 2 ]. BCL-2 was initially identified from the breakpoint of the t(14;18) chromosomal translocation found in over 60 % of indolent B cell non-Hodgkin’s lymphoma [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…BCL-X L has been implicated as a key survival factor in numerous solid tumors [ 2 ]. Based on the evidence that cancer types with BCL2 and MCL1 amplification are more prone to inhibition of their encoded proteins, we hypothesized that cancers with a significant frequency of BCL2L1 amplification are more dependent on BCL-X L for survival.…”
Section: Introductionmentioning
confidence: 99%